Clippings of a lifetime of intervention inspired by Paulo Freire (Cadernos de Sociomuseologia, 2022)
The author presents his testimony about an intervention experience of a socio-educational nature, started in 1985, in the Algarve (extreme south of Portugal), with a small group of people, based at the Escola Superior de Educação de Faro (initially , the RADIAL Project and, from 1988 onwards, the Associação in Loco). The narrative is built by reference to Paulo Freire's thought, which was present throughout the processKeywords: Paulo Freire; Socioeducation; Algarve; In-Loco